METHODOLOGY FOR CONDUCTING PRACTICAL CLASSES IN GEOGRAPHY LESSONS - Toshpo‘latov Shomurod Noraliyevich (Web of Journals Publishing, 2024)
The article reveals the content and essence of the development of the skills of observation, diligence, logical thinking, creative activity and the implementation of knowledge in everyday life through practical training of students in geography lessons. Examples are given on the organization of practical training and methods of solving issues.
Keywords: practical assignment, map, educational project, geographical issues, logical thinking, creative activity, ability, method.